PHARMACIST COUNSELING EFFECT TO THE LEVEL OF PATIENT KNOWLEDGE WITH TYPE 2 DIABETES MELLITUS IN â€œKIMIA FARMA KAWIâ€ PHARMACY, MALANG CITY - Hakim, Abdul; Atmaja, Ria Ramadhani Dwi; Sugihantoro, Hajar; Mufidah, Fahda Dina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Diabetes mellitus is a carbohydrates, fats, protein metabolism disorder that caused by impaired insulin secretion, insulin disruption or both. Diabetes mellitus sufferer need a special care to make the blood glucose level always in normal condition and no complications in various organs. Type 2 diabetes mellitus is inception of disease begins with development of key metabolic abnormality, insulin resistance. Causes of type 2 diabetes mellitus is obesity, age over 40, lifesyle, genetic suscetibility. Pharmacist counseling to the patients of type 2 diabetes mellitus is very important because it can improve patient knowledge, patient compliance to the treatment and the quality of patients life. The purpose of this study is to determine the effect of counseling by pharmacists to the level of patientâ€™s knowledge of type 2 diabetes mellitus in â€œKimia Farma Kawiâ€ Pharmacy, Malang City.This research is a quantitative study with Pre-Experimental design in the form of pretest â€“ post-test design. Number of samples was taken during one month by using consecutive sampling method. The result of this study was using through Wilcoxon test that there was difference of value before and after the pharmacist counseling the patients of type 2 diabetes mellitus with significance value equal to 0.000 (p value 0,05). The conclusion of this research is the pharmacist counseling can improve patient knowledge of type 2 diabetes mellitus.Â Keywords : pharmacist counseling, knowledge, type 2 diabetes mellitusÂ